Teachers’ Hand Gestures as Visual Cues in the English Teaching and Learning Process - Anggraeni, Ajeng; Basikin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the hand gestures of English teachers during lessons in two junior high schools in Tasikmalaya, concentrating on their varieties, frequency, and their impact on student learning. We collected data through teacher interviews, classroom observations, and qualitative content analysis of gestures. The research utilized Systemic Functional Multimodal Analysis, appraisal theory, and a gesture framework for data analysis. Findings reveal that teachers utilized representational, metaphorical, deictic, and evaluative gestures, adapting their use to students’ proficiency levels, with beginners receiving more gestures. These intentional hand gestures helped understanding, accommodated diverse learning styles, and increased student engagement, highlighting gestures' vital role in effective teaching and learning